ANALISIS KADAR ALKOHOL PRODUK KOMBUCHA DAUN PERMOT (Passiflora foetida L.) ASAL MAKASSAR SULAWESI SELATAN SECARA KROMATOGRAFI GAS - Herwin Herwin; Rachmat Kosman; Fitriani Fitriani (As-Syifaa Jurnal Farmasi, 2013)
Preliminary research permot leaf (Passiflora foetida L.) used Acetobacter xylinum bacterial culture and Sacharomyces cerevisiae yeast fermentation in determined the alcohol content of kombucha with the purpose of determined the alcohol content of kombucha products permot leaf (Passiflora foetida L.) from Makassar in South Sulawesi gas chromatography. Based on result of research fermentation of kombucha product from permot leaf by add glucose 100 gram and inoculum kombucha 10 % obtaired content by gas chromatography as big as 0,0627292 %.                                                                                     Keyword : Permot leaf, kombucha, alcohol, gas chromatography